2004
DOI: 10.1158/0008-5472.can-03-3307
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Simian Virus 40 DNA Sequences in Human Lymphoid and Hematopoietic Malignancies and Their Relationship to Aberrant Promoter Methylation of Multiple Genes

Abstract: The simian polyoma virus SV40 has been detected in specific human tumors including non-Hodgkin's lymphomas, although a causative role for the virus has not been convincingly demonstrated. Aberrant methylation of CpG islands in promoter regions is a frequent method of silencing tumor suppressor genes (TSGs) in cancers and may be induced by oncogenic viruses. We investigated the relationship between the presence of SV40 or EBV DNA sequences and the methylation profiles for 10 TSGs in 90 cases of non-Hodgkin's ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 21 publications
5
47
0
Order By: Relevance
“…Using PCR and subsequent Southern blotting, we have successfully demonstrated the presence of SV40 DNA sequences in 56% of DLBCLs in Tunisian patients prevalence, which is at the higher end of those reported from other countries. [12][13][14][15][16][17][18][19][20][21] However, these findings are at variance with those presented by other investigators, [22][23][24] who did not detect SV40 DNA in any of the lymphomas samples analyzed. This discrepancy in SV40 detection in lymphoma between several parts of the world is not clear, but it could be at least in part due to differences in laboratory techniques used for virus detection, the criteria of requirements for confirmation of the presence of virus, 1,19,22,54,56 the characteristics of patients populations that were the source of specimens 1,54 and mainly the difference in histological types of lymphomas tested.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Using PCR and subsequent Southern blotting, we have successfully demonstrated the presence of SV40 DNA sequences in 56% of DLBCLs in Tunisian patients prevalence, which is at the higher end of those reported from other countries. [12][13][14][15][16][17][18][19][20][21] However, these findings are at variance with those presented by other investigators, [22][23][24] who did not detect SV40 DNA in any of the lymphomas samples analyzed. This discrepancy in SV40 detection in lymphoma between several parts of the world is not clear, but it could be at least in part due to differences in laboratory techniques used for virus detection, the criteria of requirements for confirmation of the presence of virus, 1,19,22,54,56 the characteristics of patients populations that were the source of specimens 1,54 and mainly the difference in histological types of lymphomas tested.…”
Section: Discussionmentioning
confidence: 62%
“…28 One interesting recent study has reported a correlation between promoter hypermethylation of several TSGs and the presence of SV40 DNA in a heterogeneous group of leukemias and lymphomas, suggesting that SV40 might cause DNA methylation of TSGs. 15 In this study, we investigate the presence of SV40 DNA sequences in 108 cases of DLBCLs from patients from Tunisia and correlate the data with methylation status of a panel of 13 TSGs known or suspected to be altered by hypermethylation in several cancers including lymphomas. These tested genes included those involved in cell-cycle regulation (p14, p15, p16, p53 and RB1), cell invasion and adhesion (APC and CDH1), DNA repair and detoxification (MGMT and GSTP1), apoptosis (DAPK), B-cell differentiation (SHP1) and cell growth (p300 and BLU).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation associated with bacterial or viral infection is a well-known cause of methylation of some genes. [22][23][24] In some cases, DAPK methylation conceivably might have been induced by pneumonia or tuberculous pleuritis. In addition, a reported observation that hypermethylation of 6 genes including RASSF1A, p16, and DAPK was absent in 8 peritoneal fluid DNA samples from patients with ovarian cysts supports our speculation that inflammation is associated with methylation of some genes.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Previous reports, however, have failed to demonstrate any correlation between P53 accumulation in diffuse large B-cell lymphomas and several oncogenic viruses, including Epstein-Barr virus. [18][19][20] Several studies from the United States, [21][22][23] Japan, 24 Costa Rica, 25 and Taiwan 26 have successfully detected simian virus 40 (SV40) DNA by PCRbased methods in variable proportions of nonHodgkin's lymphomas, mainly diffuse large B-cell lymphomas, ranging from 11 to 62% of cases. We have recently 27 reported a high prevalence of SV40 in diffuse large B-cell lymphomas occurring in Tunisian patients (56%), and we noted that the presence of SV40 was significantly correlated with aberrant promoter hypermethylation of several tumor suppressor genes, suggesting a functional effect of this virus in those lymphomas.…”
mentioning
confidence: 99%